Perlindungan Hukum terhadap Korban Pelecehan Seksual dilihat dari Segi Hukum Internasional - Juliandi Juliandi; Putri Yasmin; Reh Bungana (Universitas Muhammadiyah Enrekang, 2023)
Violence against women and children as vulnerable can occur in all situations, that is when conflict takes place, the process of escape, and in refugee camps. The International Rescue Committee conducted a survey in 2015 which showed that 40% of 190 women and girls in Dara’a and Quneitra had experienced sexual violence from personnel of International Organizations when accessing humanitarian assistance services. Sexual violence that occurs in Syria is an act of sexual violence with abuse of power, or abuse of trust, for the purpose of sexual satisfaction, as well as to gain profits in the form of money, social, political and etc. Based on Article 7 Paragraph (1) Rome’s Statute of The International Criminal Court, sexual violence is a crime against humanity which is included in the category of the Most Serious Crime, so The International Law has a role in this matter. This research is a normative juridical study, which discusses the principles and concepts of International Law concerning the position of International Organizations as Subjects of International Law which have Legal Personality and Legal Capacity. Therefore it is necessary to know the arrangements related to sexual violence in international law.